Contribuição ao estudo da aderência entre barras de aço e concreto reforçado com fibras por meio do ensaio de viga - Couto, Jamille Cândida Cunha (2016)
The fundamental condition to reinforced concrete like a building material is the bond between steel and concrete.The phenomenon of bond works as a transfer mechanism of efforts and allows the strain compatibility in the steel-concrete interface. This work aims to study the bond of steel bars embedded in plainfiber reinforced concrete. Beam test was employed in accordance with RILEM RC5 (1982). Steel bars had 10 mm diameter and fibers were hooked-end with aspect ratio of 80. The fiber volume fraction 1% and the concrete compressive strength 30 MPa. The tests results show that for the fiber content employed the bond strength increase. The theoretical bond-slip models were confronted with experimental values.